Orobanche arpica (Orobanchaceae): a new species from the Caucasus, and contributional notes on O. ser. Krylowianae - Piwowarczyk, Renata; Pedraja, Óscar Sánchez; Moral, Gonzalo Moreno; Góralski, Grzegorz; Kwolek, Dagmara; Denysenko-Bennett, Magdalena; Pawełek, Barbara (Phytotaxa, 2018)
Orobanche arpica (Orobanchaceae) is described as a new, probably Caucasian endemic, species from the Lesser Caucasus in Armenia. It grows on a subalpine meadow, where it parasitises Psephellus pulcherrimus (Asteraceae). The newly-described species morphologically and phylogenetically belongs to species from the Orobanche subsect. Curvatae, apparently to species of the O. ser. Krylowianae, however it is clearly distinct. A detailed description, illustrations, a comparison with the similar species with identification key, and phylogenetic analysis are provided. We also present additional phylogenetic (O. inulae) and phytogeographic (O. mlokosiewiczii) contributions to the series Krylowianae.